Children's scale errors are a natural consequence of learning to associate objects with actions: A computational model. Issue 4 (13th December 2018) - Grzyb, Beata J.; Nagai, Yukie; Asada, Minoru; Cattani, Allegra; Floccia, Caroline; Cangelosi, Angelo
Abstract: Young children sometimes attempt an action on an object, which is inappropriate because of the object size—they make scale errors. Existing theories suggest that scale errors may result from immaturities in children's action planning system, which might be overpowered by increased complexity of object representations or developing teleofunctional bias. We used computational modelling to emulate children's learning to associate objects with actions and to select appropriate actions, given object shape and size. A computational Developmental Deep Model of Action and Naming (DDMAN) was built on the dual‐route theory of action selection, in which actions on objects are selected via a direct (nonsemantic or visual) route or an indirect (semantic) route. As in case of children, DDMAN produced scale errors: the number of errors was high at the beginning of training and decreased linearly but did not disappear completely. Inspection of emerging object–action associations revealed that these were coarsely organized by shape, hence leading DDMAN to initially select actions based on shape rather than size. With experience, DDMAN gradually learned to use size in addition to shape when selecting actions. Overall, our simulations demonstrate that children's scale errors are a natural consequence of learning to associate objects with actions. Abstract : Our Developmental model of Action and Naming (DDMAN), similarly to children, produced scale errors. Scale errors were frequent at the beginning of training and decreased linearly; after training DDMAN sporadically produced scale errors. Inspection of developing representations showed that these were coarsely organized by shape, causing the initial oversight of object size during action selection; gradually the model learned to attain to size.